(untitled) (Simbiótica. Revista Eletrônica, 2023)
ABSTRACT: This essay’s goal is to use Antoine Berman’s method, presented on Pour une critique des traductions: John Donne(1995), to criticize the translation made by João Paulo Matedi Alves (2014) of the elegy 1.9, by Tibulus; and, therefore, contribute with the steem of the discursive genre (Translation Criticism) designated by Berman. In order to do this, an short introduction about the elegiacal genre (mostly according to the book L’elegie erotique romaine, by Paul Veyne [1985]) and about Berman’s method will be made, to, subsequently, write our own criticism.